Progress of G Protein-Coupled Estrogen Receptor in Cardiovascular System Diseases - Peng, Xiaoyi (International Journal of Public Health and Medical Research, 2024)
Cardiovascular disease is one of the leading causes of death worldwide, and estrogen is thought to play a protective role in cardiovascular health. The mechanism of action and clinical significance of GPER, as an emerging class of estrogen receptors, in the cardiovascular system is being extensively studied. This elucidation of the signaling pathways and specific roles of GPER in cardiovascular diseases, i.e., the multiple roles of GPER in cardiovascular protection through the activation of multiple signaling pathways, provides new hopes and strategies for the prevention and treatment of cardiovascular diseases. The purpose of this article is to summarize the progress of research on GPER in the field of cardiovascular disease.